OP0204 Clonal Expansion of CD4+ Cytotoxic T Lymphocytes in IGG4-Related Disease. (15th July 2016) - Mattoo, H.; Mahajan, V.; Maehara, T.; Della Torre, E.; Deshpande, V.; Zachary, W.; Kulikova, M.; Stone, J.H.; Pillai, S.
Abstract : Background: IgG4-related disease (IgG4-RD) is a systemic condition of unknown etiology, characterized by highly fibrotic lesions with dense lymphoplasmacytic infiltrates rich in IgG4+ plasma cells and CD4+ T cells (1). Given the longstanding history of atopy that characterizes a proportion of patients with IgG4-RD, it has been suggested that TH2 cytokines contribute to the pathogenesis of this condition (2). However, we recently demonstrated that allergic manifestations are not increased in patients with IgG4-RD compared to the general population (3). Similarly, CD4+TH2 cells are expanded only in the peripheral blood of IgG4-RD patients with concomitant atopy, questioning the hypothesis of IgG4-RD as a TH2 driven condition (4). Objectives: We aimed to characterize CD4+ T cell subsets in IgG4-RD subjects. Methods: We used flow cytometry to identify CD4+ effector/memory T cells as well as Th1, Th2, and T regulatory cells in a cohort of 101 IgG4-RD patients. Gene expression analysis was used to further characterize expanded cells. Results were validated by flow cytometry. Next-generation sequencing of the T cell receptor β chain gene was performed on CD4+ T cells in a subset of patients to identify their clonality. Tissue infiltration by specific T cells was examined using quantitative multi-color imaging. Results: CD4+ effector/memory T cells with a cytolytic phenotype (cytotoxic T lymphocytes (CTLs)) were expanded in IgG4-RD patients compared to healthy controls. Next-generation sequencing revealed prominent clonal expansions of these CD4+CTLs but not of CD4+GATA3+ memory TH2 cells in subjects with IgG4-RD. The dominant T cells infiltrating a range of inflamed IgG4-RD tissue sites were clonally expanded CD4+CTLs that expressed granzyme A and perforin. Clinical remission induced by rituximab-mediated B cell depletion was associated with a reduction in disease-associated CD4+ CTLs. Conclusions: IgG4-RD is prominently linked to clonally-expanded CD4+ CTLs in peripheral blood as well as in inflammatory tissue lesions. A TH2 signature might be primarily linked to a concomitant atopic diathesis. CD4+ CTLs might be of pathogenic importance in other fibrotic conditions including IgG4-RD. References: Della-Torre E, Lanzillotta M, Doglioni C. Immunology of IgG4-related disease. Clin Exp Immunol. 2015 Aug;181(2):191–206. Kamisawa T, Anjiki H, Egawa N, Kubota N. Allergic manifestations in autoimmune pancreatitis. Eur J Gastroenterol Hepatol. 2009 Oct;21(10):1136–39. Della Torre E, Mattoo H, Mahajan VS, Carruthers M, Pillai S, Stone JH. Prevalence of atopy, eosinophilia, and IgE elevation in IgG4-related disease. Allergy. 2014 Feb;69(2):269–72. Mattoo H, Della-Torre E, Mahajan VS, Stone JH, Pillai S. Circulating Th2 memory cells in IgG4-related disease are restricted to a defined subset of subjects with atopy. Allergy. 2014 Mar;69(3):399–402. Disclosure of Interest: None declared